Methylenetetrahydrofolate reductase deficiency and low dietary folate reduce tumorigenesis in Apcmin/+ mice. Issue 6 (27th January 2009) - Lawrance, A K; Deng, L; Rozen, R
Abstract : Background: Clinical studies suggest that mild methylenetetrahydrofolate reductase (MTHFR) deficiency and high dietary folate may reduce the risk for colorectal cancer. There is concern, however, that high folate intake (a consequence of food fortification) may enhance tumour growth in individuals with pre-existing tumours or genetic predisposition to tumorigenesis. Aim: To determine if Mthfr deficiency and low dietary folate influence tumorigenesis in mice genetically predisposed to form numerous intestinal adenomas ( Apc min/+ ). Methods: Male Apc min/+ mice were mated with Mthfr +/− and/or Mthfr +/+ females. Diets with variable folate content were administered either pre-natally or at weaning; tumours were counted in offspring at 10 weeks of age. Plasma homocysteine and levels of apoptosis, DNA methylation and nucleotide ratios (dUTP:dTTP) in normal (pre-neoplastic) intestine were measured. Results: Apc min/+ mice fed high folate diets from weaning developed more adenomas than those fed the folic acid-deficient diet (FADD) or the control diet (CD); Mthfr deficiency did not affect adenoma number. However, when the FADD and CD were administered to dams prior to conception, throughout pregnancy and continued in offspring post-weaning, Apc min/+ offspring fed FADD developed fewer adenomas than those fed CD. Mthfr +/− genotype of the mother or of the offspring also reduced adenoma numbers in the Apc min/+ offspring. Adenoma number was inversely correlated with plasma homocysteine (r = −0.49, p<0.005, intestinal dUTP/dTTP ratios (r = −0.42, p = 0.05), and levels of intestinal apoptosis (r = −0.36, p = 0.08). Conclusions: Low dietary folate and Mthfr deficiency reduce adenoma formation in mice predisposed to tumorigenesis, possibly through increased apoptosis consequent to hyperhomocysteinaemia and nucleotide imbalances.